Respuesta :

Answer:

C.),F.),andD.) Are correct

Step-by-step explanation:

Answer:

Option: C, D and F are the correct options.

C.   [tex](\dfrac{36}{4})^x[/tex]

D.   [tex]9\cdot 9^{x-1}[/tex]

F.  [tex]\dfrac{36^x}{4^x}[/tex]

Step-by-step explanation:

We are asked to find the expression which is equivalent to:

                                        [tex]9^x[/tex]

C)

 [tex](\dfrac{36}{4})^x[/tex]

We know that:

[tex](\dfrac{36}{4})^x=9^x[/tex]

Since, 36/4=9

Hence, option: C is correct.

D)

[tex]9\cdot 9^{x-1}=9^{1+x-1}[/tex]

Since,

[tex]a^m\cdot a^n=a^{m+n}[/tex]

Hence,

[tex]9\cdot 9^{x-1}=9^x[/tex]

Hence, option: D is correct.

F)

[tex]\dfrac{36^x}{4^x}[/tex]

We know that:

[tex]\dfrac{36^x}{4^x}=(\dfrac{36}{4})^x[/tex]

Since, we know that:

[tex]\dfrac{a^n}{b^n}=(\dfrac{a}{b})^n[/tex]

Hence, we have:

[tex]\dfrac{36^x}{4^x}=9^x[/tex]

Since, 36/4=9

Hence, option: F is the correct answer.